ASYLUM RECEPTION CENTRE IN CYPRUS: SETTING THE BASES FOR A CONTEMPORARY ORGANISATIONAL STRUCTURE - Spaneas, Stefanos; Cochliou, Despina (European Scientific Journal, ESJ, 2013)
The purpose of this article is to present the living conditions and services provided at Kofinou Asylum Reception Centre in Cyprus through a Project funded by the European Refugee Fund and the Republic of Cyprus. It is based on the knowledge gained, when an academic institution initiated the operational transformation of the Centre towards an organisational structure that would adopt modern principles of organisational management, parallel to the provision of comprehensive social welfare support. The main presenting pillars include details about a) The provision of counselling and supporting services, which were provided to the residents of the centre b) Administrative support for the daily operation and c) The design and implementation of educational and recreational activities. Emphasis was drawn upon the strengths, weaknesses, opportunities and threats that were identified. It is suggested that both residents and staff’s active participation provided opportunities for those involved to investigate possible individual and organisational transformation over time, as participative ‘bottom-up’ approaches of organisational learning are generated. The knowledge generated could be used as a paradigm to lead policy-makers and central administration to accept the development of cross-system thinking and planning. It is also expected that decision-making flexibility will be increased through constant feedback from the bottom to the upper level and vice versa.